Constrained active contours for boundary refinement in interactive image segmentation - Anh, Nguyen Thi Nhat (2013)
The state-of-the-art interactive image segmentation algorithms are often not able to produce accurate segmentation results with one-shot user input, and they frequently rely on laborious user editing to refine the segmentation boundary. In this paper, we propose a constrained active contour method for boundary refinement, which can be used to improve the segmentation results of many existing region-based interactive segmentation algorithms. Our constrained active contour model exhibits many desired properties for a good boundary refinement tool, including the robustness to user inputs, the ability to produce a smooth and accurate boundary contour, and the ability to handle topology changes. Experimental results show that the proposed refinement tool is highly effective and can significantly improve initial segmentation results without additional user inputs.